Development of Mobile Learning Media Using Ispring Suite on Course of Waste Management Technology - Edwin Sutiana, - (2021)
Learning activities in Waste Management Technology courses are carried out with material explanations and presentations between student goups.learning media used in this Waste Management Technologyis also minimal and monotonous so that learning feels a little bpring. This learning optimization can be done by developing innovative learning media as a means of student self-study. Mobile learning media was developed using ispring suite.The purpose of this research is knowing feasibility of mobile learning media using ispring suite on course of Waste Management Technology. The development of this instructional media uses the ADDIE model,Tthe stages include Analyze, Design, Development, Implementation, and Evaluation. Evaluations is carried out by making improvements to learning media based on suggestions from material experts, media experts and students responses. The results indicate that mobile learning media are declared "eligible" by material experts and declared "very eligible" by media experts, and also declared "very eligible" by students responses with a 81,40% eligibility percentage. Based on these results, through the assessment of material experts, media experts and student responses, it can be concluded that this mobile learning media on course of Waste Management Technology is suitable for use as learning media in the Agro-industrial Technologi Educaton study program.